ANALISIS ALOKASI BIAYA BERSAMA UNTUK MENENTUKAN HARGA POKOK PRODUKSI PADA UD. VANELA - Farahdiba, Farahdiba; Mogi, Grace B.; Walandow, Stanly Kho (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
Joint cost is the cost that processing together at the same time as the cost of direct labor and factory overhead costs to produce multiple product. To determining of joint cost need to calculation the cost of production, that purpose was to calculate and determining supply of external report, the aim of this research is to doing analysis the allocation of joint cost in determining cost of production on Vanela. The method of this research is relative sales value method. The final conclution is that the joint cost allocation is based on a comparison table that difference in cost allocation is different because Vanela take into account the overall cost of the product to the product so the cost should be allocated costs of each product are not allocated according to the calculation of cost allocation, and for the calculation of joint cost is according with the allocation of costs that should be. If using the relative sales value method the cost of allocation becomes more obvious as it should be and based on the book.